2020
DOI: 10.1186/s12909-020-02119-z
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a coach: experiences of faculty educators learning to coach medical students

Abstract: Background: Despite the growth of coaching in medical education, many questions remain about the process of becoming a coach for medical students. We sought to understand the process through which faculty acclimated to this new role, and what benefits and challenges they experienced. Methods: A multi-phase qualitative focus group study was conducted with 20 faculty at one medical school in the United States during the initial year coaching was implemented. Focus group transcripts were analyzed using the consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 20 publications
(34 reference statements)
4
22
0
9
Order By: Relevance
“…Faculty found that using coaching skills motivated and empowered their learners in a way that felt personally fulfilling to themselves. They expanded their professional identities to embrace their new roles as coaches, aligning with previously reported findings in the literature [ 14 ]. By being intrinsically motivated to continue their professional development and working to change the learning culture within GME, they, in many ways, co-produced the goal of coaching.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Faculty found that using coaching skills motivated and empowered their learners in a way that felt personally fulfilling to themselves. They expanded their professional identities to embrace their new roles as coaches, aligning with previously reported findings in the literature [ 14 ]. By being intrinsically motivated to continue their professional development and working to change the learning culture within GME, they, in many ways, co-produced the goal of coaching.…”
Section: Discussionsupporting
confidence: 81%
“…To date, few residency transition programs have harnessed the benefits of coaching to address the needs of graduating students and interns [ 12 , 13 ]. Furthermore, there is limited data around the experiences of faculty coaches as they switch over to a coaching role from more traditional roles in GME [ 14 ]. The aim of this work is to describe our experiences developing faculty educator coaches for a UME to GME transition program.…”
Section: Main Text Introductionmentioning
confidence: 99%
“…A prior study found that medical student coaches struggled when there was uncertainty about how to structure coaching sessions and about how flexible they could be. 20 Significantly, the coaches in our study noted an improvement in their own teaching skills. Prior studies have found that faculty peer observers perceive their observation of other faculty teaching to benefit them as well.…”
Section: Discussionsupporting
confidence: 48%
“…Both Elster et al's and Brooks et al's studies of medical student coaches revealed similar themes that could contribute to a coach's professional satisfaction or fulfillment, such as guiding struggling trainees, building a longitudinal relationship, and observing their successes [6,7]. Coaches in both studies were challenged by the fragmentation of one's professional identity due to the coaching role and the expectations and burden this carried.…”
Section: Discussionmentioning
confidence: 92%
“…The research on coaching in medicine has focused on coachees and only recently have the experiences of coaches been explored. A 2020 qualitative study by Brooks et al of medical student coaches identified both professional benefits (helping struggling students, providing holistic guidance) and challenges (unclear expectations of the role, balancing between coaching and supervising) [6]. A mixed methods study from 2021 by Elster et al found that a higher proportion of medical student coaches was burned out compared to physician faculty with administrative roles.…”
Section: Introductionmentioning
confidence: 99%